A red-to-near-infrared fluorescent probe for the detection of thiophenol based on a novel hydroxylflavone-quinoline-amino molecular system with large Stokes shift. (June 2021) - Wu, Qingqing; Wang, Jianbo; Liang, Wenlang
Abstract: In this work, we synthesized a novel long-wavelength-emitting fluorophore FQ-OH based on a novel designed hydroxylflavone-quinoline-amino molecular system with both intramolecular charge transfer (ICT) and excited-state intramolecular proton transfer (ESIPT) process, enabling FQ-OH with strong fluorescence in a wide range of 550–800 nm, covering red-to-near-infrared emission region and large stokes shift as much as 162 nm. Due to the promising spectra property, FQ-OH was then fabricated into a red-to-near-infrared fluorescent probe FQ-DNP for the selective detection of thiophenol via aromatic nucleophilic substitution (SN Ar) reaction mechanism. Spectra assays in the solution demonstrated that FQ-DNP displayed prominent turn-on fluorescence response to thiophenol in 550–800 nm with emission peak at 627 nm, excellent selectivity, and exceptional sensitivity (detection limit as low as 7.2 nM). In addition, thiophenol in vapor form could be detected by FQ-DNP coated test papers enabling naked eye detection. Moreover, FQ-DNP was utilized for detecting thiophenol in environmental samples and showed great recovery results. Furthermore, biological application of FQ-DNP in living cells through cell imaging study demonstrated apparent intracellular fluorescence enhancement before/after thiophenol addition. Graphical abstract: Image 1 Highlights: A red-to-near-infrared fluorescent probe FQ-DNP for the selective detection of thiophenol was obtained. FQ-DNP displayed excellent selectivity and exceptional sensitivity (detection limit as low as 7.2 nM). Thiophenol in vapor form could be detected by FQ-DNP coated test papers enabling naked eye detection. Detection of thiophenol in environmental samples by FQ-DNP showed great recovery results. FQ-DNP demonstrated apparent intracellular fluorescence enhancement before/after thiophenol addition.